Discursive construction of ‘user innovations’ in the open source software development context - Iivari, Netta (Information and organization, 2010)
This paper analyzes the discursive construction of user innovations in open source software (OSS) development. A review of the literature on user innovation is conducted, after which a refined conceptualization of this topic encompassing the Foucauldian and social shaping of technology traditions is offered. A discourse analytic approach is used to examine both the process and the outcome of user innovation. Through an interpretive case study, a set of discourses evolving within an OSS project's website is identified, each implying particular subject positions for the OSS users and OSS developers in software production and consumption processes. Particular kinds of subject positions for the OSS users are adopted, negotiated, opposed as well as created by the OSS users in the analyzed discourses. The developers are in an authoritative position as the decision-makers and the ones realizing the innovations, but the users are allowed important positions of co-creators and co-cultivators. User innovation is characterized as a continuous, evolving co-creation process of the modes of subjectivity offered for the OSS users. This kind of process could be experimented with in other kinds of development contexts. On the other hand, this study questions many assumptions related to user innovation that are taken for granted, highlighting the difficulty of simply and straightforwardly enhancing it in any context. Finally, implications for theory and practice are discussed.